2012
DOI: 10.1097/fpc.0b013e3283544062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P450 oxidoreductase variants on the metabolism of model substrates mediated by CYP2C9.1, CYP2C9.2, and CYP2C9.3

Abstract: POR variants affect CYP2C9 activities. The impact of a POR variant on catalysis varies with the isoform of CYP2C9 and the assay substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
2
34
2
Order By: Relevance
“…The fact that losartan pharmacokinetics is affected by the CYP2C9*3 polymorphism, but not by CYP2C9*2, could be explained because *3 allele codes for an enzyme with lower activity than the one by *2 allele. In this sense, subjects with *2 allele have an intermediate activity phenotype and *3 allele carriers showed a low activity phenotype (Subramanian et al, 2012). In addition, other studies have shown pharmacokinetic associations with CYP2C9*3 but not with CYP2C9*2 (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that losartan pharmacokinetics is affected by the CYP2C9*3 polymorphism, but not by CYP2C9*2, could be explained because *3 allele codes for an enzyme with lower activity than the one by *2 allele. In this sense, subjects with *2 allele have an intermediate activity phenotype and *3 allele carriers showed a low activity phenotype (Subramanian et al, 2012). In addition, other studies have shown pharmacokinetic associations with CYP2C9*3 but not with CYP2C9*2 (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Four different cDNA expression systems have been successfully used for the in vitro drug metabolism studies, including bacteria [22], yeast [23], insect cells [24] and mammalian cells [13]. Compared with other expression systems, mammalian cells have adequate endogenous OR and cytochrome b 5 to support CYP activities and are much closer to the inherent environment of human proteins; thus, it is much more relevant to assess the potential effects of recombinant human CYP variant proteins in the mammalian cell system [21].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [10] has characterized the impact of a single common POR SNP, A503V, on the activity of the CYP3A5*1/*1 and CYP3A5*3/*3 genotypes in vivo. Two studies in reconstituted systems revealed different effects on CYP2C8 variants [21] and CYP2C9 variants [22]; however, these studies were performed with a very limited number of POR mutations and CYP isoforms. Human liver microsomes (HLMs) provide a valuable means to test the effect of POR polymorphisms on CYP activity because they contain the enzymes in their native environment.Unfortunately, no studies on the activities of different CYP genotypes have been conducted with HLMs.…”
Section: Introductionmentioning
confidence: 99%